1999
DOI: 10.1046/j.1439-0264.1999.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Das postnatale Wachstum des Skeletts und der Körpermasse beim Beagle

Abstract: Growth of beagles is described on the basis of body weight and 14 bone measures. Eighteen male and 19 female dogs were investigated at 14 different ages from birth to the 13th month of life. Characteristics of the growth curves were evaluated using the modified Janoschek growth curve. For the classification into dwarfish, low, normal, big and gigantic growth, the growth curves are presented with percentiles. The arithmetic means and standard deviations for both sexes are presented in tables. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…They observed a higher growth rate in the hindlimbs than the forelimbs and no sex difference in growth termination. In contrast to the studies mentioned above [22,23] and in accordance with Hawthorne et al [24], who investigated body mass development in different breeds, Salomon et al [21] concluded that larger breeds grow for a longer time.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…They observed a higher growth rate in the hindlimbs than the forelimbs and no sex difference in growth termination. In contrast to the studies mentioned above [22,23] and in accordance with Hawthorne et al [24], who investigated body mass development in different breeds, Salomon et al [21] concluded that larger breeds grow for a longer time.…”
Section: Introductionmentioning
confidence: 71%
“…Schulze and colleagues [22,23] studied four breeds and a greater number of individuals per breed compared to Weise [18]; similarly, they observed that larger breeds differ from smaller breeds in their growth rates rather than growth duration. Salomon et al [21] monitored 14 measurements of 37 Beagles during the first 13 months. They observed a higher growth rate in the hindlimbs than the forelimbs and no sex difference in growth termination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regressions of postcranial dimensions and various skeletal measurements relative to body mass have been used for estimating body size in a wide variety of mammals [3] . Therefore, it has been possible to form a logical estimate of the body weight and size and morphologies of animals [6][7][8][9][10] . Although dental and craniometric measurements, which are more intensively studied and easily available in archaeological sites, have been more frequently used [11,12] , especially in both extant and extinct carnivores, it has been accepted that osteometric measurements of the long bones provide more reliable estimates of body mass [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Although dental and craniometric measurements, which are more intensively studied and easily available in archaeological sites, have been more frequently used [11,12] , especially in both extant and extinct carnivores, it has been accepted that osteometric measurements of the long bones provide more reliable estimates of body mass [6] . Various scholars have used different formulations based on diameters and circumference of the long bones [1,6,8,10,[13][14][15][16][17][18] . Therefore, body weight has been estimated by using these measures.…”
Section: Introductionmentioning
confidence: 99%